Electrostatic precipitator design with wire-cylinder electrodes as a particulate matter reduction - Siregar, Yulianta; Debataraja, Bio; Soeharwinto, Soeharwinto; Mubarakah, Naemah; Dinzi, Riswan (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Small industries are inseparable from the production of gaseous pollutants. One of the contents of exhaust gases produced from small industrial activities is particulate matter. The consequences of exposure to particulate matter for too long are coughing, cancer, blood coagulation, and death. For this reason, a tool is needed to capture particulate matter in small industrial exhaust gases. Based on the problems described, this research proposes using the electrostatic precipitator with the cockroft-walton method because this method is very effective in capturing particulate matter. The research results on electrostatic precipitator (ESP) with a pair of electrodes will achieve an efficiency of 25.4% when the voltage regulator is 20 V, while the efficiency is 98.7% when the voltage regulator is 35 V. The ESP with two pairs of electrodes will achieve 99.5% efficiency when the voltage regulator is 30 volts. Installing a vibrator as a particle thresher at the electrode is unsuitable for low-temperature exhaust gases because it produces a liquid and sticky residue that makes it difficult to fall off.